Analysis of scientific-methodical approaches to assessing the impact of hostilities on land productivity from scientific-methodical approaches to assessing the impact of hostilities on land productivity - Butenko, Y.; Kharytonenko, R.; Petrychenko, S. (Land Management, Cadastre and Land Monitoring, 2023)
A review and analysis of government methodological recommendations, studies of scientific institutions, groups of scientists and public organizations related to studies of the assessment and impact of hostilities on the ground was carried out.  The key positions in methodological recommendations related to the assessment of negative consequences on land due to man-made pollution and damage are selected and indicated.  The key positions in the methodological recommendations related to the assessment of negative consequences on the ground as a result of hostilities were analyzed and indicated.The study of scientific institutions, groups of scientists and public organizations related to studies of the assessment and impact of hostilities on lands and soils is considered.  It is indicated that the practical studies to date, which are related to the assessment of the impact of hostilities on the productivity of land use, in particular, in terms of the territories of territorial communities, are spot-on.  It is noted that the government's methodological recommendations, dedicated to land in general or in the context of agricultural land, forest fund and do not take into account other categories of land.  The need to continue scientific research and the development of methodological recommendations regarding the assessment and restoration of land as a result of hostilities was emphasized, and relevant directions were proposed.Key words: assessment of land quality, assessment of soil quality, consequences of hostilities on lands and soils, productive potential.
Keywords: assessment of land quality; assessment of soil quality; consequences of hostilities on lands and soils; productive potential.